A Case of Fulminant Meningococcemia: It Is All in the Complement - Kellie L. Hawkins; Mariah Hoffman; Sonia Okuyama; Sarah E. Rowan (Case Reports in Infectious Diseases)
Eculizumab is a novel monoclonal antibody that inhibits complement-mediated hemolysis in patients with paroxysmal nocturnal hemoglobinuria (PNH). Complement deficiency is a well-known risk factor for meningococcal infection. We describe a case of a young patient with PNH treated with eculizumab who presented with a life-threatening case of nongroupable meningococcemia. As this new biologic agent becomes more widely prescribed, providers should be aware of the increased risk of meningococcemia. In addition to vaccination, providers may consider the use of oral penicillin for antibiotic prophylaxis against Neisseria meningitidis in these cases of functional complement deficiency.